2016
DOI: 10.1681/asn.2014121214
|View full text |Cite
|
Sign up to set email alerts
|

Double-Negative αβ T Cells Are Early Responders to AKI and Are Found in Human Kidney

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 33 publications
(36 reference statements)
7
80
7
Order By: Relevance
“…DN T cells are rare in the peripheral blood and lymphoid organs but comprise a significant component of renal T cells accounting for 18 to 32% of resident T cells in both mouse and humans [25]. Renal DN T cells expand significantly in early phase of AKI, express higher level of IL-10 and IL-27 compared to conventional T lymphocytes, and adoptive transfer of DN T cells reduce ischemic AKI in mice.…”
Section: Immune Cells In Aki Repairmentioning
confidence: 99%
“…DN T cells are rare in the peripheral blood and lymphoid organs but comprise a significant component of renal T cells accounting for 18 to 32% of resident T cells in both mouse and humans [25]. Renal DN T cells expand significantly in early phase of AKI, express higher level of IL-10 and IL-27 compared to conventional T lymphocytes, and adoptive transfer of DN T cells reduce ischemic AKI in mice.…”
Section: Immune Cells In Aki Repairmentioning
confidence: 99%
“…In a mouse warm IRI mode, both pre-treatment and post-treatment of mouse anti-thymocyte globulin increased the percentage of DN T cells but had no obvious effect on kidney injury [40]. Recently, Martina et al [41] indicated that DN T cells were an important subset of the resident T-cell population in the mammalian kidney with anti-inflammatory properties and served as the responders to AKI. It might be interesting if we had investigated the proportion of DN T cells before and after CD28sa administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other suppressive cells not belonging to the Th lineage include CD3 + CD4 − CD8 − double‐negative T cells, Qa‐1‐restricted CD8 Tregs and CD28 lo CD8 + Tregs . While these additional regulatory T‐cell subsets have not been as well studied as the conventional CD4 + Foxp3 + Tregs that are discussed in this review, there is evidence for their protective involvement in renal disease …”
Section: Subsets Of Suppressive T Cellsmentioning
confidence: 97%
“…[127][128][129] While these additional regulatory T-cell subsets have not been as well studied as the conventional CD4 + Foxp3 + Tregs that are discussed in this review, there is evidence for their protective involvement in renal disease. 27,123,[130][131][132]…”
Section: Subsets Of Suppressive T Cellsmentioning
confidence: 99%